Biomechanical evaluation of spring system for implant-supported prosthesis: analysis by photoelasticity and extensometry - Goiato, Marcelo Coelho [UNESP] (2017)
New systems are released in the odontological market with the objective of bringing improvements and advancements in the clinical success of implants and implant-supported prostheses. The distribution of tension for the bone/implant system of these new systems is important. The purpose of this work was to evaluate, by photoelastic analysis and strain gauges, the distribution of tension for the bone/implant system, using the Slim system. A photoelastic cast with an external hexagon implant was manufactured and a metal prosthesis was screwed below it, with or without the tested system. For the photoelasticity methodology, a photoelastic cast, with or without the tested system, was positioned in a circular polariscope, and axial loads of 100 N were applied to the centre of the crown. The pattern of tension generated was photographed and analysed qualitatively in an imaging programme. For the extensometry methodology, two extensometers were placed in the mesial and distal region of the implant in the photoelastic cast. The axial loads were applied to the group again, with or without the system (n = 10). The t test of independent samples with a significance level of 5% was used for this analysis. This study demonstrated greater tension values for both the photoelastic and extensometry methods when the tested system was used. Clinical studies must be performed to evaluate the tested system because the results might not be clinically significant to a bone reabsorption.